Evolution of oscillator spectrum in periodic potential - Buts, V.A.; Yegorov, A.M.; Marekha, V.I.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2007)
Spectral power of the oscillator radiation, which moves in periodically inhomogeneous potential, is investigated analytically and numerically. Spectrum of the nonrelativistic oscillator can have a maximum at high numbers of harmonics of basic frequency. Amplitudes of potential at which the motion of oscillator become irregular are found. In relativistic case a small value of potential practically not influence on character of spectrum. The dependence of high-frequency range of spectrum from value of potential inhomogeneity period is investigated. With decreasing of inhomogeneity period the spectrum maximum is shifting into short-wave range. In linear approximation the dispersion equation for oscillation excitation by ensemble of oscillators at frequency, which corresponds to the maximum of radiation spectrum of single oscillator is found.